PENGARUH KOMPETENSI INTELEKTUAL, KOMPETENSI EMOSIONAL, KOMETENSI SOSIALTERHADAP KOMITMEN NORMATIFDIMODERASI BUDAYA HIRARKI DI PT. INDONESIA POWER UP SEMARANG - Danik Muadziyani, 13.05.51.0195 (Students' Journal of Economic and Management, 2017)
This study aims to examine the influence of competence on organizational commitment moderated organizational culture in PT. Indonesia Power UP Semarang. This research is included intothe quantitative data by using primary data obtained from the questionnaire.The method used in this study is in the form of questionnaires where the total population of as many as 100 employees, while the data are processed permanent employees. Measurement using Likert scale with 5 (five) alternative answers. Test instrument used is coefficient of determination (R2) and test of F (Goodness Of Fit). Hypothesis test in this research use regression analysis.The result of regreai analysis is known that competence significantly influence organizational commitment moderated by organizational culture. The results of the analysis revealed that intellectual competence, emotional competence, social competence together affect the organizational commitment.Keywords: Competence, Organizational Commitment and Organizational Culture